Perancangan Film Pendek Animasi 2D ‘Broken’ Sebagai Media Penyampai Pesan - Raphael Theofilus Santoso; Saiful Yahya (LPPM STIKI Malang, 2023)
Anime animation often raises complex social issues, one of which is bullying. Anime animation is one of the most popular animations in Indonesia, one of which is from high school students, where during high school or school bullying often occurs. Bullying is an aggressive act committed by someone, either physically or verbally. This act is repeated and there is a difference in strength between the perpetrator and the victim. The design of this animation work aims to convey a message to high school students or equivalent to anime-style visuals. The story is based on the perspective of a bully who has experienced bullying in other cases. Animation design using the Creation Process 2D animated movie method, designed by Moreno. The method consists of 3 stages, namely pre-production, production and post-production. The pre-production stage consists of the compiler of the Idea and Script, Character Design and Storyboard. The production stages consist of Storyboard, Voice Over, Animate and Background. The post-production stage consists of Compositing. This study received a positive response from the target audience, with the results of 87.8% stating that they agreed and deserved as an animated film that could convey bullying content from the perceptive bully.